Z-DNA: vacuum ultraviolet circular dichroism. - Sutherland, J C (1981)
In concentrated salt or ethanolic solutions, the self-complementary copolymer poly(dG-dC).poly(dG-dC) forms a left-handed double-helical structure that has been termed "Z-DNA." The first evidence for this structure came from changes observed in the circular dichroism (CD) spectrum between 230 and 300 nm for low- and high-salt solutions (Pohl, F. M. & Jovin, T. M. (1972) J. Mol. Biol. 67, 675-696). In 3 M NaCl, the CD spectrum is approximately inverted compared to the B-form spectrum observed in low-salt solution. We measured the vacuum ultraviolet CD spectrum of poly(dG-dC).poly(dG-dC) down to 180 nm under conditions in which the 230- to 300-nm spectrum is inverted. Below 200 nm, where the B form exhibits the large positive peak at 187 nm that is characteristic of right-handed double-helical DNAs, the Z form exhibits a large negative peak at 194 nm and a positive band below 186 nm. Therefore, the Z-form vacuum ultraviolet CD spectrum resembles an inverted and red-shifted B-form spectrum. The magnitudes of the differences observed between the B and Z forms in the CD spectrum below 200 nm are about 10 times greater than those observed between 230 and 300 nm. The vacuum ultraviolet CD spectrum of poly(dG-dC).poly(dG-dC) in 3 M Cs2SO4 also is inverted compared to the B-form spectrum; however, between 230 and 300 nm, it is nonconservative with a negative maximum at 290 nm and a weak positive CD signal above 300 nm, presumably reflecting differential light scattering and indicating the existence of molecular aggregates. Our results suggest that the vacuum ultraviolet CD spectrum is sensitive to the handedness of double-helical DNA structures. The CD spectrum in this region should complement other spectroscopic methods in relating the structures of poly(dG-dC).poly(dG-dC) existing in solution to those determined in the solid state by x-ray crystallography.